Ambient Lighting in the Reading Room: Theoretical Concepts and Practical Outcomes - A. Brennan, John; Brennan, Patrick; Miner Haygood, Tamara (Current Medical Imaging, 2010)
Much research has focussed on optimisation of acquisition of diagnostic images, whilst relatively little work has been done on optimising the reading environment. We discuss the physiology of vision, particularly regarding light adaptation, and its impact on image interpretation. With this background in mind, we then discuss the issue of ambient light in the reading room. Research by our group and others suggests that optimal reading room lighting may be close to 50 lux.
Keywords: perception